2016
DOI: 10.3109/13880209.2015.1074254
|View full text |Cite
|
Sign up to set email alerts
|

The ginsenoside metabolite compound K exerts its anti-inflammatory activity by downregulating memory B cell in adjuvant-induced arthritis

Abstract: (2016) The ginsenoside metabolite compound K exerts its anti-inflammatory activity by downregulating memory B cell in adjuvant-induced arthritis, Pharmaceutical Biology, 54:7, 1280-1288, DOI: 10.3109/13880209.2015 PHARMACEUTICAL BIOLOGY, 2016 VOL. 54, NO. 7, 1280-1288 http://dx.doi.org/10.3109/13880209.2015 ORIGINAL ARTICLEThe ginsenoside metabolite compound K exerts its anti-inflammatory activity by downregulating memory B cell in adjuvant-induced arthritis + (memory B cells) and expression of CD40 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…1). Interestingly, compound K (40 mg/kg and 160 mg/kg per os) exerted an antiinflammatory activity by suppressing memory B cell subsets, CD40L expression on T cells and CD40 expression on B cells in a rat model of adjuvant induced arthritis (Chen et al, 2016a).…”
Section: Immune Systemmentioning
confidence: 99%
“…1). Interestingly, compound K (40 mg/kg and 160 mg/kg per os) exerted an antiinflammatory activity by suppressing memory B cell subsets, CD40L expression on T cells and CD40 expression on B cells in a rat model of adjuvant induced arthritis (Chen et al, 2016a).…”
Section: Immune Systemmentioning
confidence: 99%
“…Ginsenoside compound K is one of the active metabolites of Panaxnotoginseng saponins [ 6 ]. Studies have indicated that ginsenoside compound K has multiple pharmacological activities, including inhibition of the proliferation of cancer [ 7 , 8 ] and smooth muscle cells [ 9 ], activation of glucocorticoid receptors [ 10 ], anti-inflammation [ 11 ], and so on. Besides the above biological effects, our previous study has shown that ginsenoside compound K could attenuate the formation of atherosclerosis in mice via activating LXRα [ 12 ], without presentation of the serious side effects caused by synthetic unspecific LXRs agonists, such as the elevation of plasma triglycerides [ 13 ] and liver steatosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polysaccharides of AG exerted immunostimulant and suppressed lipopolysaccharide immune response under basal and lipopolysaccharide actuated proinflammatory conditions in lab rats [47]. Strikingly, compound K (40 mg/kg and 160 mg/kg per os) exerted an anti-inflammatory effect by suppressing memory B cell subsets, CD40L expression on T cells and CD40 expression on B cells in a lab rat model of adjuvant induced arthritis [48]. Immunological investigations showed that AG could prominently expand phagocytosis of macrophages, encourage nitric oxide generation, Tumor necrosis factor-α and interleukin-6 creation.…”
Section: Effects On the Immune Systemmentioning
confidence: 98%
“…Communally AG extract concentrate is a potential method to surmount the diabetic state and it has vasodilator effects [91]. It merits bringing up that compound K and ginsenoside Rb1 are responsible for the same effects on glucose metabolism credited to AG preparations [48,114].…”
Section: Effects On Metabolismmentioning
confidence: 99%